Does Chronic Inflammation Play a Role in Rheumatic Mitral Valve Restenosis after Percutaneous Transvenous Mitral Commissurotomy? - Butarbutar, Maruli; Firman, Doni; Ariani, Rina; Alkatiri, Amir Aziz; Wicaksono, Sony Hilal; Soesanto, Amiliana M. (Jurnal Kardiologi Indonesia, 2022)
Background: Mitral valve restenosis is defined as decreased mitral valve area (MVA) <1.5 cm2 or decreased MVA >50% after PTMC. It is time-dependent and associated with major adverse cardiovascular events (MACE), such as congestive heart failure, cardiac death, mitral valve replacement, and redo PTMC. The mechanism is not yet known; however, chronic inflammation may have a role. This research aims to determine the association between chronic inflammation and mitral valve restenosis after PTMC. Methods: A total of 40 patients with mitral valve stenosis who underwent successful PTMC were matched and classified into restenosis/case group (n=20) and no restenosis/control group (n=20). Secondary data was taken from electronic medical records such as patient characteristics (gender, age & 2nd prophylaxis), echocardiography data before PTMC (Wilkins’ score and MVA before PTMC), and echocardiography data after PTMC (MVA after PTMC). Follow-up echocardiography examination (follow-up MVA) and laboratory assessment of chronic inflammation marker (IL-6) were done on all patients. Statistical analyses were done to look for an association between the level of chronic inflammation marker & other independent variables with mitral valve restenosis. Results: Median IL-6 concentration was 2.39 (0.03 – 11.4) pg/mL. There was no statistically significant difference in IL-6 levels between both groups (p-value >0.05). MVA decrement was 0.13 (0 – 0.62) cm2/year with rate of MVA decrement ≥0.155 cm2/year was predictor of mitral valve restenosis (p-value <0.001, OR = 46.72, 95% CI 6.69 – 326.19). Conclusion: Chronic inflammation assessed by IL-6 was not associated with mitral valve restenosis.This article has a related Erratum.